Comparison of Laparoscopic and Open Surgery in Cholecystectomy for Complicated Cholelithiasis - Martins Abreu, Daniela Bruna (2024)
Cholecystectomy, whether laparoscopic or open, is the standard treatment for complicated cholelithiasis. Laparoscopic surgery has gained popularity due to its benefits, such as shorter recovery time and reduced postoperative pain. This article aims to conduct a systematic review of the current medical literature, following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, to identify the efficacy and safety of laparoscopic surgery compared to open surgery in cholecystectomy for complicated cholelithiasis. The research was conducted in the PubMed, Cochrane, LILACS, and SciELO databases, covering the last five years (2018-2023). The search strategy included the terms “Laparoscopic Cholecystectomy,” “Cholecystectomy,” and “Cholelithiasis,” with five studies selected to compose the systematic review. The results obtained demonstrated that laparoscopic surgery is associated with a lower rate of postoperative complications, shorter hospitalization time, and faster recovery compared to open surgery. However, open surgery is still preferred in cases of complex anatomy or severe complications. It was concluded that laparoscopic surgery is a safe and effective option for most cases of complicated cholelithiasis, providing significant benefits in terms of recovery and patient quality of life.